2018
DOI: 10.1089/jayao.2017.0110
|View full text |Cite|
|
Sign up to set email alerts
|

A Life Put on Pause: An Exploration of the Health-Related Quality of Life Issues Relevant to Adolescents and Young Adults with Cancer

Abstract: A wide spectrum of both negative and positive issues were described. Several of these issues, such as disrupted life plans and difficulty establishing romantic relationships, are likely to be more common to AYAs with cancer and might not be captured by existing HRQoL measures. Recognition of these issues and finding ways of addressing them should be seen as an essential component of AYA-tailored cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 28 publications
3
66
0
Order By: Relevance
“…Our findings relating to the impact of cancer on education for AYAs replicate what we previously found (Sodergren et al, ) as well as other research (Ang et al, ; Chiang, Yeh, Wang, & Yang, ; Sandeberg, Johansson, Björk, & Wettergren, ) and features in measures used with young people such as the PedsQL (Varni, Burwinkle, Katz, Meeske, & Dickinson, ). It was also not surprising that the impact on education was more obvious for younger participants as they were mostly currently enrolled in education or had to suspend their education following their diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings relating to the impact of cancer on education for AYAs replicate what we previously found (Sodergren et al, ) as well as other research (Ang et al, ; Chiang, Yeh, Wang, & Yang, ; Sandeberg, Johansson, Björk, & Wettergren, ) and features in measures used with young people such as the PedsQL (Varni, Burwinkle, Katz, Meeske, & Dickinson, ). It was also not surprising that the impact on education was more obvious for younger participants as they were mostly currently enrolled in education or had to suspend their education following their diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…To identify whether certain HRQoL concerns are more prominent amongst AYAs (14–25 years), we invited AYAs and older adults (26–60 years) to be interviewed. As part of the interview, participants were asked to review the relevance and importance of a list of HRQoL issues generated from AYAs aged 14–25 years (Sodergren et al, ) as well as issues captured from a systematic review of the literature on AYA oncology (Sodergren et al, ). The list included 77 issues organised according to the following categories: symptoms (physical, cognitive) ( n = 12 issues); activity restrictions (including disrupted life plans) ( n = 7); social (interactions with family and friends) ( n = 14); emotional ( n = 12); body image ( n = 3); self‐appraisals (how one feels about oneself) ( n = 7); outlook on life (including priorities) ( n = 9); lifestyle ( n = 5); treatment‐related (including treatment burden) ( n = 5) and life beyond treatment ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, increased awareness has led to further research into the clinical and psychosocial needs of this group, including their health‐related quality of life (HRQOL) . Prior work suggests that unmet psychosocial needs include a need for information about cancer, infertility, and nutrition .…”
Section: Introductionmentioning
confidence: 99%
“…Prior work suggests that unmet psychosocial needs include a need for information about cancer, infertility, and nutrition . Qualitative and quantitative studies have identified areas of particular concern to AYAs, including symptoms, physical activity, relationships with others, fertility, body image, spirituality, and cognitive function (work or school) . However, previous studies have often focused on survivors rather than newly diagnosed patients and have not always explored priorities by age within the AYA group .…”
Section: Introductionmentioning
confidence: 99%
“…While there are many reports of the measurement of HRQL attributed to this population, concerns have been raised about the suitability of the instruments used for this purpose, such as the absence of domains for sexuality and spirituality . In a study undertaken by the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Group, the results of interviews with 45 AYAs aged 14‐25 were reported recently . The categories of issues pertinent to HRQL were symptoms, activity limitations, disrupted life plans, adverse social impact, emotional morbidity, changes in body image, positive self‐appraisals, outlook on life, restrictions on lifestyle, treatment‐related sequelae, fertility and financial concerns.…”
Section: Hrql In Ayas With Cancer – Suitability Of Instrumentsmentioning
confidence: 99%